Some continuous stress mixed formulations and inf-sup test - Szemplińska-Stupnicka, Wanda; Tyrkiel, Elżbieta; Zubrzycki, Andrzej (Computer Assisted Methods in Engineering and Science, 2001)
The most frequent motivation for the use of mixed methods is their robustness in the presence of certain limiting and extreme situations. At variance, the main goal of the present paper is to reconsider the use of mixed formulation as a tool for wider application, i.e., to study the stability of the proposed procedure treating problems in elasticity otherwise well suited for the solution by the usual displacement method. Computational procedure for the inf-sup test is outlined, and the results are given.